MEMBANGUN KINERJA KARYAWAN MELALUI MOTIVASI KERJA, KAPABILITAS SUMBERDAYA MANUSIA, DAN ORGANIZATIONAL CITIZENSHIP BEHAVIOR PADA KOPERASI ARTHAGUNA PURWODADI - Feny Larasati; Rini Handayani (Riset Manajemen dan Akuntansi, 2022)
All organizations will certainly make every effort to fix and improve the quality of the performance of their employees, one of which is through good management of human resources. To achieve the goals of an organization, the thing that managers need to do is provide encouragement so that employees can work according to what the organization wants. KSP Artha Guna is a company engaged in savings and loan cooperatives. KSP Artha Guna is one of the best cooperatives in Purwodadi city. and the developing savings and loan cooperative has several branches in Grobogan. To find out the positive and significant influence of Motivation, Human Resource Capability, and Organizational Citizenship Behavior on Employee Performance in Arthaguna Purwodadi Cooperative. This type of research will be conducted by the author using a qualitative research approach with the case study method. The sample in this study was 78 respondents from administrators and members of the Arthaguna Purwodadi cooperative with a sampling technique using survey methods. To analyze the research data used a statistical test T test with SPSS version 25.00 with test results stating that H1 is accepted means that work motivation partially affects the performance of KSP Arthaguna Purwodadi employees. That H2 is accepted means that the capability of human resources partially influences the performance of KSP Arthaguna Purwodadi employees. That H3 is accepted means that the Organizational Citizenship Behavior partially influences the performance of KSP Arthaguna Purwodadi employees.